Semantic Approach to Antonyms in Q.S Al-Hadid The Perspective of Muhammad ‘Ali Al-Khūlī - Syahadi, Fajar (Yayasan Salam Cerdas Al-Fattah, 2024)
This study aims to analyze the use of antonyms (at-taḍād) in Q.S Al-Hadid with a semantic approach based on the thoughts of Muhammad ‘Ali Al-Khūlī. The method used is a literature study with a qualitative descriptive approach, which focuses on an in-depth analysis of the linguistic and theological meaning of the antonyms found in the surah. The results of the study reveal that the use of antonyms in Q.S Al-Hadid is not just a variation of language, but has an important role in strengthening the theological message conveyed. These antonyms help highlight the duality of concepts such as the world and the hereafter, life and death, and light and dark, which ultimately affirm the oneness of God. The semantic approach developed by Muhammad ‘Ali Al-Khūlī provides deeper insight into the relationship between the duality of meaning and understanding of the divine nature, where antonyms function as a tool to emphasize the fundamental differences between the worldly and the hereafter dimensions. Thus, this study emphasizes the importance of semantic analysis in understanding the profound messages contained in the Qur'an.